Two new species of Borreria (Spermacoceae, Rubiaceae) from the states of Goiás and Minas Gerais, Brazil - Miguel, Laila Mabel; Souza, Elnatan; Cabral, Elsa Leonor (Phytotaxa, 2015)
Two new species of Borreria from Goiás and Minas Gerais are described and illustrated. Borreria minensis was found in “campos rupestres” formation, between 1100 and 1600 m elevation, and is endemic to Minas Gerais, while Borreria psyllocarpoides was found in the “cerrado” vegetation, at the border of Goiás and Minas Gerais. Electron microphotographs of the seeds and pollen grains, and a distribution map of the two new species are also provided.